Upaya Guru dalam Meningkatkan Kreativitas Peserta Didik Melalui Pembelajaran SBDP - Wardan, Annisa Indah; Ningrum, Kharisma Septia; Amelia, Reza; Prakus, Septri (Indonesian Journal Publisher, 2024)
Students' creativity in SBdP learning at the basic education level aims to develop awareness of art or beauty because teachers have great difficulty testing students' creativity. Infrastructure is still minimal, so it greatly influences the process of teaching and learning activities. This can be seen from the lack of interest of students to be creative when teachers carry out teaching and learning activities in class. The aim of this research is to analyze teachers' efforts to increase students' creativity in SBDP learning in elementary schools. This research is research using a qualitative approach. The results of the research show that there are several obstacles for teachers in increasing students' creative thinking, namely teachers not being able to utilize technology well, lack of infrastructure, teachers' abilities are still low, and teachers are less creative in making teaching materials. The efforts made by teachers in dealing with problems are respecting the ideas expressed by students, teachers can stimulate students' creativity during learning, and teachers must respect questions or answers from students. The implication of this research is that it is hoped that teachers can use SBDP learning to see students' creative abilities level.